Bromination of hydrocarbons with CBr4, initiated by light-emitting diode irradiation - Nishina, Yuta; Ohtani, Bunsho; Kikushima, Kotaro (Beilstein Journal of Organic Chemistry, 2013)
The bromination of hydrocarbons with CBr4 as a bromine source, induced by light-emitting diode (LED) irradiation, has been developed. Monobromides were synthesized with high efficiency without the need for any additives, catalysts, heating, or inert conditions. Action and absorption spectra suggest that CBr4 absorbs light to give active species for the bromination. The generation of CHBr3 was confirmed by NMR spectroscopy and GC–MS spectrometry analysis, indicating that the present bromination involves the homolytic cleavage of a C–Br bond in CBr4 followed by radical abstraction of a hydrogen atom from a hydrocarbon.
Keywords: bromination; free radical; hydrocarbon; light-emitting diode; photo irradiation